Huygens' Metasurface Based on Induced Magnetism: Enhance the Microwave Absorption Performance of Magnetic Coating. Issue 12 (7th March 2022) - Zhang, Tuo; Duan, Yuping; Huang, Lingxi; Pang, Huifang; Liu, Jiangyong; Ma, Xinran; Shi, Yupeng; Lei, Hao
Abstract: Despite great efforts in material design and modification, there are still obstacles to improve the effective microwave absorption, which hinders the development of stealth materials. By introducing a magnetically induced Huygens' metasurface with Fibonacci spiral meta‐atom, a hierarchical absorber with carbonyl iron particle coating is designed and prepared, of which the total effective absorption bandwidth (EAB, reflection loss ≤− 10 dB) amazingly reaches 9.41 GHz, exceeding 199% of the original coatings', and the absorption peak value declines from − 15.91 to − 32.12 dB. The overall thickness of the absorber is 7 mm, only 0.17 over the minimum thickness dictated by the causality limit. A conceptual basis for the proposed design is provided, that is, the balance of effective surface current and magnetic current induced simultaneously will enhance the electromagnetic (EM) wave transmission, which contributes to broadening the absorption bandwidth with promising impedance matching. The system is validated numerically and experimentally, suggesting a novel route to obtain high‐performance microwave absorption materials for the EM stealth technology. Abstract : A hierarchical microwave absorber composed of magnetic induction Huygens' metasurface (HMS) and magnetic coating is designed and prepared. The balance of effective surface current and magnetic current induced by HMS can enhance the electromagnetic wave transmission, which contributes to broadening the absorption bandwidth with promising impedance matching. This conceptual design suggests a novel route to obtain high‐performance absorbing materials.